Filament interaction modeled by flux rope reconnection - Török, T. (2011)
Hα observations of solar active region NOAA 10501 on 2003 November 20 revealed a very uncommon dynamic process: during the development of a nearby flare, two adjacent elongated filaments approached each other, merged at their middle sections, and separated again, thereby forming stable configurations with new footpoint connections. The observed dynamic pattern is indicative of "slingshot" reconnection between two magnetic flux ropes. We test this scenario by means of a three-dimensional zero β magnetohydrodynamic simulation, using a modified version of the coronal flux rope model by Titov and Démoulin as the initial condition for the magnetic field. To this end, a configuration is constructed that contains two flux ropes which are oriented side-by-side and are embedded in an ambient potential field. The choice of the magnetic orientation of the flux ropes and of the topology of the potential field is guided by the observations. Quasi-static boundary flows are then imposed to bring the middle sections of the flux ropes into contact. After sufficient driving, the ropes reconnect and two new flux ropes are formed, which now connect the former adjacent flux rope footpoints of opposite polarity. The corresponding evolution of filament material is modeled by calculating the positions of field line dips at all times. The dips follow the morphological evolution of the flux ropes, in qualitative agreement with the observed filaments. © 2011. The American Astronomical Society. All rights reserved. Printed in the U.S.A.